Complete chloroplast genome of a medicinal species Polygonatum kingianum in China (Asparagaceae, Asparagales). Issue 1 (2nd January 2020) - Jin, Jian; Lao, Jia; Zhong, Can; He, Wei; Xie, Jing; Hu, Guoan; Liu, Hao; Yan, Fulin; Zhang, Shuihan
Abstract: Polygonatum kingianum is a medicinal and food plant distributed in most of countries throughout the temperate Northern Hemisphere. Here we report on the complete chloroplast (cp) genome sequence of P. kingianum . The cp genome is 155, 399 bp in size and includes two inverted repeat regions of 52, 7411 bp, which is separated by a large single-copy region of 84, 234 bp and a small single copy region of 18, 424 bp. A total of 130 genes were predicted, including 38 tRNA, 8 rRNA, and 84 protein-coding genes. Phylogenetic analysis placed P. kingianum under the subfamily Nolinoideae of the family Asparagaceae.